Existence of ground state solutions to Dirac equations with vanishing potentials at infinity - Figueiredo, Giovany M.; Pimenta, Marcos T.O. [UNESP] (Elsevier, 2017)
In this work we study the existence of ground-state solutions of Dirac equations with potentials which are allowed to vanish at infinity. The approach is based on minimization of the energy functional over a generalized Nehari set. Some conditions on the potentials are given in order to overcome the lack of compactness.
Keywords: Dirac equation; Variational methods